Hepatite lobular dissecante em dois caninos Golden Retriever não relacionados geneticamente - Argenta, Fernando Froner; Hobbhahn, Sissy; Witz, Maria Ines; Fallavena, Luiz Cezar Bello; Esmeraldino, Anamaria Telles (Acta Scientiae Veterinariae, 2017)
Background: Lobular dissecting hepatitis (LDH) is a rare condition of unknown etiology occurring in individuals or in litters of young dogs from some breeds, having poor prognosis and short survival time. Clinically, ascites, weight loss, anorexia, diarrhea and acquired portosystemic shunts are present. Hepatic encephalopathy may also occur. Biochemical blood tests usually show elevated ALT levels. Macroscopically, the liver shows changes in volume, color and regeneration nodules. Histologically, dissection of the parenchyma by connective tissue proliferation leads to disorganization of the liver architecture. The aim of this article is report LDH in two Golden Retriever dogs genetically unrelated. Cases: Two dogs genetically unrelated and of different owners - Golden Retriever breed - were referred to the Veterinary Medical Teaching Hospital of the Universidade Luterana do Brasil (ULBRA). The first case was a female with 17 months of age and the second, brought to examination one year later, was a male with nine months of age. The clinical signs, in both animals were similar, consisting in intense prostration, inapetence, caquexia and ascites for approximately two weeks. The female dog presented also ataxia, convulsion and diarrhea. Blood examination showed, for both dogs, arregenerative anemia, normal levels of alanine aminotransferase (ALT) and elevated levels of alkaline phosphatase. Total serum protein and albumin were also reduced. Both dogs were euthanized due to their critical condition. The necropsy showed similar lesions in both animals: approximately one liter of a free red colored fluid was observed in the abdominal cavity and hepatic changes consisting in pale green color, smooth surface, firm consistence, yellowish nodules at the surface and tissue proliferation at the margins. There was also congestion of the abdominal visceral veins (portal shunts). Histopathological examination showed, for both dogs, interstitial diffuse fibrosis causing dissection of the parenchyma and isolating hepatocytes in small groups, marked cholestasis and sinusoidal infiltration of inflammatory cells (mainly lymphocytes and plasma cells). Discussion: Lobular dissecting hepatitis is a rare form of hepatic cirrhosis, being unique only to dogs. Some breeds including German Shepherd, Poodle, Rottweiler, Cocker Spaniel and Golden Retriever are considered susceptible to the disease. The clinical signs, age, breed and macroscopic and microscopic lesions presented by the two dogs were consistent with LDH. In this disease, serum biochemistry analyses generally show hypoalbuminemia and increased levels of hepatic enzymes, mainly the ALT. In both animals herein described, albumin levels were decreased, but ALT levels were normal, indicating that a suspicion of this disease should not be discarded in similar cases. ALT levels, as well as of other hepatic enzymes, may not reflect the severity of chronic hepatopathies like LDH, in which the producer cells of this enzyme are being destroyed. These two animals, in spite of pertaining to the same breed, did not presented any genetic relationship, and were owned by different persons. The disease may have a great number of possible etiologies and historical data from the two dogs herein described did not indicated any relevant aspect which could be implicated as a cause of the condition. As affected animals are generally referred to a veterinary consultation in an advanced condition, the cause is difficult to be determined.